Design and Analysis of Power-function-sine Flexure Hinges - Li Jiabiao; Zhao Yang; Wu Qingwen; Mu Deqiang; Liu Changru; Hu Jinxin (Jixie chuandong)
In this study, a new type of power-function-sine flexure hinge is proposed. The calculation formula of compliance and rotation accuracy of the flexure hinge is derived by using Castigliano's second theorem. The finite element simulation analysis and theoretical value calculation of compliance and rotation accuracy are carried out by taking different parameter values. The relative error is less than 10%, which verifies the correctness of the calculation formula. The influence of curve equation parameters of the flexure hinge on the performance of the flexure hinge is analyzed. The results show that the minimum thickness has the greatest influence on the performance of the flexure hinge. In addition, the ellipse and hyperbola are compared with the new hinge. The results show that the ellipse flexure hinge has the greatest compliance, but the rotation accuracy is the smallest; the hyperbolic flexure hinge has the highest rotation accuracy, but the lowest compliance. By introducing the compliance accuracy ratio β, through analysis and comparison, it is known that under the same L and the changing d, the value of the power function sine flexure hinge β is 2.68 times and 1.237 times higher than those of elliptical and hyperbola flexure hinges respectively. With the same flexure hinge diameter and the changing length, the value of the power function of sinusoidal flexure hinge β is 2.60 times and 1.18 times higher than that of elliptic and hyperbolic flexure hinges respectively. It shows that the power function sinusoidal flexure hinge has more advantages in comprehensive performance.